What drives food price volatility? Evidence based on a generalized VAR approach applied to the food, financial and energy markets - Sławomir Śmiech; Monika Papież; Marek A. Dąbrowski; Kamil Fijorek (Kiel Institute for the World Economy (IfW), 2018)
The aim of this study is to investigate sources of food prices volatility. The analysis uses daily series for volatility of corn, soybean, wheat, rice, US dollar, crude oil, and SP500 futures spanning the period January 4, 2000 to April 1, 2017. The authors employ the generalized vector autoregressive framework in rolling sample approach in order to capture the time-varying nature of volatility spillovers. The results reveal that: volatility spillovers measures change over time; most of the volatility spillovers are observed within the two groups of markets: food markets and 'non-food' markets; corn market is net volatility transmitter.
https://dx.doi.org/10.7910/DVN/RQOZIJ
Keywords: Q17; G15; C58; 330; volatility spillovers; food markets; financial and energy markets; generalized VAR; lasso estimation